Role of Peer Coaching in Transmitting the Benefits of Leader Coaching - Dong, Yanan; Dong, Huijuan; Yuan, Yuan; Jiang, Jing (Frontiers in Psychology, 2022)
Drawing on social information processing theory, the present study examines how and when leader coaching can be beneficial for team performance. Based on a sample of 58 teams from a sanitary product company in China, we found that peer coaching served as a mediator linking leader coaching and team performance. Moreover, team individualistic/collectivism value moderated the first-stage relationship that the relationship between leader coaching and peer coaching was more positive when team individualism value was low, but not significant when team individualism value was high; while team task interdependence moderated the second-stage relationship that the relationship between peer coaching and team performance was more positive when team task interdependence was high, but not significant when it was low. The findings enrich our understandings of the effectiveness of leader coaching behavior by uncovering the theoretical mechanism and boundary conditions. The study also provides important implications for coaching practice in organizations.